Appendicular mass – a rare form of tuberculosis - Petrișor Banu; Vlad D. Constantin; Florian Popa; Mircea Brătucu; Teodora Vlădescu; Cristian Bălălău (Journal of Mind and Medical Sciences)
Tuberculosis is in the top 10 causes of death worldwide, being one of the most deadly infectious diseases. It is estimated that one of three people from the entire earth population has a latent infection with M tuberculosis. This aerobic bacterium possesses the ability to persist in host tissues for years and to begin replication once immunity declines. The lungs are most frequent site of infection as the Mycobacterium tuberculosis is carried by aerosol droplets and is commonly transmitted by respiratory route. The second way of transmission is by contaminated food. Intestinal contamination coexists with pulmonary tuberculosis and only 10% represent primitive enteric diseases. The ileocecal region is involved most frequently. Even in this context isolated appendicular involvement remains rare. We report the case of appendicular tuberculosis in a 17-year-old woman with no evidence of other location of disease elsewhere in the body.